Development of protein enriched cold extruded pasta products using hybrid dried processed mushroom powder and defatted flours: A study on nutraceutical, textural, colour and sensory attributes. (1st December 2022) - Thomas, Binuja; Sudheer, Kundukulangara Pulissery; Saranya, S.; Kothakota, Anjineyulu; Pandiselvam, Ravi; Joseph, Michael
Abstract: Standardisation of the formulation for the development of three categories of protein enriched ready -to -cook (RTC) pastas (defatted coconut-based pasta, soya-based pasta and mushroom-based pasta) was performed. Protein enrichment using defatted coconut flour (DFC-10, 15 and 20 g/100 g, microwave combined with fluidized bed dried mushroom powder (M-5, 10 and 15 g/100 g) and defatted soya flour (DFS-20, 25 and 30 g/100 g) were incorporated in the study. Highest swelling power of 2.5 g/g to 2.9 g/g was observed for mushroom-based pasta. Whereas maximum firmness of 57.22 N was observed in soya-based pasta sample with 30 g/100 g addition level. The optimal cooking time for coconut-based pasta was least - around 6 min with 20 g/100 g inclusion. However, the solid loss of DFC pasta samples gradually increased with the incorporation of DFC flour (6.8%–12.0%). Sensory evaluation using fuzzy logic model was performed for each category and the sample M1 with 5 g/100 g inclusion of mushroom powder was standardized as the best among the mushroom-based pasta. The standardized composition in defatted coconut-based pasta and defatted soya-based pasta category were DFC1 (10 g/100 g) and S 2 (25 g/100 g) respectively. The protein enrichment by partially replacing wheat with the by-products imparted high nutritive value and acceptance to the protein enriched pasta products. Highlights: Protein-enriched pasta was prepared by using defatted coconut flour, mushroom powder and defatted soy flour. Combination of microwave and fluidized bed drying was used to produce mushroom powder with maximum nutrient retention. The pasta quality was affected by the addition levels of the protein-rich supplements. Fuzzy logic model was used to determine the pasta with best sensory properties within each supplement.